Financial Literacy, Risk Perception, Overconfidence Moderated by Financial Education on Investment Decisions - Pambudi, Titis Rena Siwi; Sudarno; Sabandi, Muhammad (Universitas Negeri Semarang, 2024)
This study aims to determine: effect of financial literacy on investment decision making; effect of risk perception on investment decision making; effect of overconfidence on investment decision making; effect of financial education on strengthening financial literacy and risk perception on Investation decision. This research uses quantitative type with investors in Surakarta as population. The sample of 160 was taken using a non probably sampling technique. Data collection techniques used a questionnaire with a Likert scale of 1-5 points and a dummy variable with a value of 0 or 1, distributed via Google form. Validity test using Confirmatory Factor Analysis (CFA) and reliability test using Cronbach Alpha. The hypothesis was tested through Hierarchical Regression after a descriptive statistical test and classic assumption test were performed. The data were processed using SPSS 25 software. The results of the study proved that (1) there was a significant positive effect of financial literacy on investment decision making; (2) there was a significant positive effect on perceived risk on investment decision making; (3) there was a significant negative effect of overconfidence on investment decision making; and (4) financial education moderates financial literacy, risk perception, and overconfidence in investment decision making.